Development Development of Land Capability-Based Settlement Areas in Banyuasin District - Een Zarlin; Ardi Arfani; Heru Wahyono (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2022)
Lack study of land capability aspects in development of residential area affect the carrying capacity of environment. Therefore, this study aimed to analyze the land capability in Banyuasin District and formulate the land use directions according to its capability class. The research method used descriptive quantitative method using a spatial analysis approach with Geographic Information System and scoring analysis. The study results found out that the LCU of morphology was classified into low morphological LCU of 96.77% and less morphological LCU of 3.23%, the LCU of ease of work was high 48.11% and low 24.83%, the LCU of slope stability with the classification of high slope stability of 48.11% nd low slope stability of 24.83%, the LCU of foundation stability with high classification of 48.11% and low classification of 24.83%, the LCU of water availability with high classification of 48.11 and very low classification of 24.83%, the LCU of drainage with high classification of 56.62% and less classification of 46.11%, the LCU of erosion with high classification of 31.80% and very low classification of 1.85%, the LCU of waste disposal with sufficient classification of 46.11% and less classification of 56.62%, the LCU of disaster prone with high classification of 48.11% and low classification of 24.83%. In conclusion, the research area was divided into 3 classes of very high, moderately high, and low land development capability.